Analisa Pengaruh dari Orientasi Pesaing, Kinerja Layanan Serta Daya Tarik Produk terhadap Kinerja Pemasaran (Studi Kasus Pengusaha UMKM Cafe dan Resto di Kota Pontianak) - Pasifikus Maisirata (LPPM Universitas Widya Dharma Pontianak, 2022)
This study aims to determine the effect of competitor orientation, service performance and product attractiveness on marketing performance at MSME Cafe and Resto in Pontianak City. The form of this research uses the causality method by using a questionnaire as a data collection method and as for the qualitative analysis tool used by the author to measure the data using a rating scale. The sample used in this study were 92 respondents from MSME Cafe and Resto in Pontianak City. The technique of collecting samples in this study is the census. The Statistical program for social science (SPSS) version 23 was used for testing the research model. The results of this study are Competitor Orientation, Service Quality and Product Attractiveness have a positive and significant effect both partially and simultaneously on Marketing Performance.Keywords: competitor orientation, service performance, product attractiveness, and marketing performance.